Tenofovir Alafenamide Rescues Renal Tubules in Patients with Chronic Hepatitis B - Tomoya Sano; Takumi Kawaguchi; Tatsuya Ide; Keisuke Amano; Reiichiro Kuwahara; Teruko Arinaga-Hino; Takuji Torimura (Life, 2021)
Nucles(t)ide analogs (NAs) are effective for chronic hepatitis B (CHB). NAs suppress hepatic decompensation and hepatocarcinogenesis, leading to a dramatic improvement of the natural course of patients with CHB. However, renal dysfunction is becoming an important issue for the management of CHB. Renal dysfunction develops in patients with the long-term treatment of NAs including adefovir dipivoxil and tenofovir disoproxil fumarate. Recently, several studies have reported that the newly approved tenofovir alafenamide (TAF) has a safe profile for the kidney due to greater plasma stability. In this mini-review, we discuss the effectiveness of switching to TAF for NAs-related renal tubular dysfunction in patients with CHB.